2018
DOI: 10.1002/ange.201713179
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed Carboacylation/Aromatization Cascade Initiated by Regioselective C−C Activation of Benzocyclobutenones

Abstract: Described here is the first example of ar hodiumcatalyzedc arboacylation/aromatization cascade of aC = O bond by CÀCa ctivation. In this transformation, ar eactive rhodaindanone complex is regioselectively generated and adds across aC =Obond with subsequent elimination, thus providing au nique strategy to access am ultisubstituted benzofuran scaffold. Ad iverse range of benzofuran analogues were obtained in good yields.M echanistic studies show at ricyclic lactone was aviable intermediate.Application of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…After chromatographic purification, compounds 1-7 (39-68% yields, respectively) were obtained as a racemic mixture (Figure) [4,. Hydroxy benzil compounds (8)(9)(10)(11)(12)(13)(14) were synthesized from hydroxy benzoins' oxidation (1-7) [72][73][74] with conc. nitric acid, PCC, and Fehling reagent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After chromatographic purification, compounds 1-7 (39-68% yields, respectively) were obtained as a racemic mixture (Figure) [4,. Hydroxy benzil compounds (8)(9)(10)(11)(12)(13)(14) were synthesized from hydroxy benzoins' oxidation (1-7) [72][73][74] with conc. nitric acid, PCC, and Fehling reagent.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the % inhibition was calculated according to the formula [1-(test substance A/solvent control A)×100. MTT on cells of increasing concentrations (1,2,4,8,16,32,64, and 128 µg / mL) of each test substance over a certain range to determine the IC 50 concentrations of test substances (concentration that inhibits the proliferation of 50% of cells in the medium) were prepared. Results were analyzed using a logarithmic function with the help of the Excel program over the logarithmic curve prepared from the absorbance values obtained after the test (Table 5).…”
Section: Anticancer Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…( Table 2). The search in CSD (Groom et al 2016) has shown that these values are from the ranges found for corresponding bond (Sun et al 2018). On the other hand, the mean values of 1.31(2) and 1.22(2) Å for C-O(H) and C=O bonds, resp., in carboxyl-syn structural fragment were reported (D'Ascenzo and Auffinger 2015).…”
Section: Crystal Structurementioning
confidence: 86%